Uniqueness of Academic Career: Voices of Malaysian Women Professors - Ismail, Maimunah (Eurojournals, 2007)
This article discusses women professors’ experience on what makes academia an attractive field for their career development. It starts by describing salient features of academic career. It then outlines the research procedures, using career history data of 31 women professors from eight Malaysian universities. Themes generated from the data are as follows: teaching is a noble duty, high value of research and publication, ability to work as academic-cum-administrator, establishment of international networking, provision of sabbatical leave, and involvement in professional training and consultancies. The study concludes that the respondents are fully satisfied with the three-in-one functions of teaching, research and services at the universities. Recommendations for policy and future research are put forth.